Sypung på rymmen: Lenngren, textåteranvändning och rekontextualiseringar - Jarlbrink, Johan (Tidskrift för litteraturvetenskap, 2024)
Sewing Pouch on the Run: Lenngren, Text Reuse, and Recontextualizations This article is tracing a newspaper poem, originally published in 1795 in the section for lost and found, and reprinted repeatedly in newspapers in the nineteenth and early twentieth century. The poem describes a girl who has lost a pouch with her sewing kit on a walk through Stockholm. The one who returns it is promised two sugar breads and a kiss as a reward. It was published anonymously but Anna Maria Lenngren was later identified as the author. Following the poem from paper to paper reveals a network of text reuse where texts were borrowed, edited and recontextualized. Several papers all around Sweden published the verse as an anonymous advertisement from 1837 to 1868. Yet, among other things, the editors also changed the place name mentioned in the poem to make it seem as if it was written by a local girl. Another version of the text was widely circulated in papers from 1887 to 1917. This version was truer to the original wording of the poem, but it was published along with an anecdote identifying Lenngren herself as the girl in the text, making it part of her own marriage proposal. This time the poem was placed in the section for humorous titbits, among gossip and funny stories. The different versions of the poem illustrate how newspapers could function as a medium for literature in the nineteenth century. The practice of text reuse had the potential of maximizing the readership but could also mean that authors lost control over their words. When poems became “fugitive verses” in the network of newspapers, they entered a fluid state where authorships were destabilized and texts were recontextualized to fit on the newspaper page.